A Model for Improving Human Resource Performance in the Context of Knowledge Donating - Wuryanti, Wuryanti; Setiawan, Indrianto (JDM (Jurnal Dinamika Manajemen), 2017)
This study aims to examine the relationship between self efficacy, social competence and knowledge donating variables on organizational performance. This research uses quantitative research method by using primary data taken from questionnaires dispersion. The population of this study is all employees who work in KPP Pratama Semarang (Office Tax) consisting of 113 respondents. While the sampling is done through the census method. Analysis technique of this research using Moderating Regression Analysis (MRA) technique. The results of this study indicate that there is a significant influence of self efficacy and social competence on performance. Thus, to improve the performance of the tax office needs to improve self-efficacy of employees, especially their readiness to risk their jobs by giving them some skills to minimize risks on the job, such as technical skills, organizational skills and leadership skills. The tax office also needs to improve the social competence, especially the sense of concern for their employees. The tax office also needs to create conditions that support fellow employees in order to willing to share new knowledge.